2019
DOI: 10.1542/peds.2018-2308
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal Antibody Treatment of RSV Bronchiolitis in Young Infants: A Randomized Trial

Abstract: BACKGROUND: Monoclonal antibody to respiratory syncytial virus (RSV; palivizumab) is recommend for prophylaxis of high-risk infants during bronchiolitis seasons but not for RSV bronchiolitis treatment. Our aim was to determine if palivizumab would be helpful in young infants with acute RSV bronchiolitis. METHODS: Eligible infants #3 months old presenting to the pediatric emergency service with RSV-positive bronchiolitis requiring inpatient admission underwent double-blind random assignment to single-dose intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 30 publications
1
21
0
2
Order By: Relevance
“…40,41 In contrast, therapeutic administration of either palivizumab or motavizumab to RSVinfected infants after hospitalization did not alter disease severity and the duration of hospitalization compared with placebotreated RSV-infected infants. 42,43 Thus, only pre-existing RSVspecific neutralizing antibodies are sufficient to reduce RSVassociated disease in humans, similar to our results reported here evaluating RSV-specific memory CD8 T cell-mediated disease in mice. Given the demonstrated ability for prophylactic administration of neutralizing antibodies to prevent RSV-associated disease in humans, it is likely that they will also be capable of mitigating potentially pathological responses mediated by human memory CD8 T cells.…”
Section: Discussionsupporting
confidence: 86%
“…40,41 In contrast, therapeutic administration of either palivizumab or motavizumab to RSVinfected infants after hospitalization did not alter disease severity and the duration of hospitalization compared with placebotreated RSV-infected infants. 42,43 Thus, only pre-existing RSVspecific neutralizing antibodies are sufficient to reduce RSVassociated disease in humans, similar to our results reported here evaluating RSV-specific memory CD8 T cell-mediated disease in mice. Given the demonstrated ability for prophylactic administration of neutralizing antibodies to prevent RSV-associated disease in humans, it is likely that they will also be capable of mitigating potentially pathological responses mediated by human memory CD8 T cells.…”
Section: Discussionsupporting
confidence: 86%
“…Palivizumab an anti-RSV antibody that binds both pre-and post-fusion forms of the RSV F protein is highly effective as prophylaxis against RSV in human infants [13]but is ineffective as antiviral treatment once infection has occurred. [14] Experiments in a cotton rat model of RSV bronchiolitis demonstrated that a combination of anti-RSV antibodies and immunomodulation with NSAIDs or steroids did improve clinical outcomes following infection in a way that monotherapy did not. [9,15] RSV fusion protein inhibitors (FPI) have shown somewhat better results in animal models.…”
Section: Introductionmentioning
confidence: 99%
“…Although effective in prevention, palivizumab has no therapeutic effect in acute RSV infection. 96 Fusion inhibitors have gained the most attention with presatovir the most recent. Presatovir has undergone five phase II trials but has limited impact on viral load and had no effect on clinical features of RSV disease; clinical trials have been halted due to safety concerns.…”
Section: Antiviral Therapymentioning
confidence: 99%